Impact of digitalization on the accumulation of social capital in the economy - Галушка, Зоя Іванівна (International Science Journal of Management, Economics & Finance., 2024)
The article substantiates the essence and peculiarities of social capital as an economic resource and identifies the positive and negative impact of digitalization on its formation and accumulation. A comparative analysis is conducted, revealing a change in approaches to substantiating the essence of social capital. The accumulation of social capital is considered in an economic context. This is a process of increasing the economic opportunities of various participants in economic relations by expanding mutual trust, shared perceptions, and adherence to norms and values. It is an important mechanism for effectively conducting economic activities, fostering trust, and ensuring long-term benefits in business. The study of the impact of digitalization on the formation of the economy's social capital is based on the study of the systemic interrelation of forms of social capital existence, spheres, methods, and mechanisms of its accumulation, and conditions of reproduction. It is noted that this process has resource, environmental, and performance characteristics.
Keywords: digitalization, social innovation, social capital, accumulation of social capital, social security, social boundaries.